Measurement Evidence for Collaboration, Feedback, Self-Efficacy, and Academic Stress in Project-Based Learning Management - Yusuf, Muhammad; Sembiring, Dian Arisandy Eka Putra; Fauzan, Muhammad; Mardiyanti, Lely; Hendra, Robi; Arif Wijaya, Hansein (FKIP Universitas Jambi, 2026)
Project-Based Learning (PjBL) has become one of the most widely adopted instructional approaches for developing twenty-first-century competencies. However, its implementation often exposes students to academic stress due to intensive collaboration, project deadlines, and continuous assessment. Although collaboration skills, lecturer feedback, self-efficacy, and academic stress have been widely investigated, evidence regarding the psychometric quality of instruments measuring these constructs within the context of PjBL remains limited. This study aimed to provide measurement evidence for four constructs associated with Project-Based Learning management among undergraduate biology education students. A quantitative instrument validation design was employed involving four expert validators for content validation and 59 students for pilot testing. Content validity was evaluated using the Item-Level Content Validity Index (I-CVI), Scale-Level Content Validity Index (S-CVI/Ave), and modified kappa coefficient (K*). Subsequently, the measurement model was assessed through Confirmatory Composite Analysis (CCA) within the Partial Least Squares Structural Equation Modeling (PLS-SEM) framework. The results demonstrated excellent content validity, with an S-CVI/Ave of 0.91 and modified kappa values ranging from 0.667 to 1.000. After refinement of indicators with low outer loadings, all constructs demonstrated satisfactory psychometric properties, including Composite Reliability values ranging from 0.89 to 0.94, Average Variance Extracted values between 0.508 and 0.633, and HTMT values below 0.85, indicating adequate convergent and discriminant validity. These findings provide empirical evidence that the instrument possesses satisfactory validity and reliability for measuring collaboration skills, lecturer feedback, self-efficacy, and academic stress within the context of Project-Based Learning. The validated instrument provides a sound foundation for future structural model testing examining the relationships among these constructs.